Internet censorship detected in Ethiopia (Ethiopia) - Voidly (2026)
CRITICAL severity censorship detected in Ethiopia. Confidence: 65%. Data sourced from CensoredPlanet.
Censorship Incident ID: ET-2026-0033
Keywords: censorship; ET; censorship; critical